Complexes of Solver Ion with Pyridines and Some Amines in Acetonitrile - J.M. Nagarkar, Mrs.; Natarajan, G.S. (Asian Journal of Chemistry, 2010)
In the present work, we report the interaction of silver ions withpyridines and some amines in non-aqueous medium with lowerdielectric constant like acetonitrile.